New scan strategy for Electron Beam Melting: Process window and microstructure evolution - Shojai, Ismail (My University, 2019)
For the Electron Beam Melting Process, point melt scan strategy is evaluated instead of using a traditional hatch scan strategy. The effect on porosity, microstructure and basic mechanical properties are investigated using TiAl6V4 alloy powder. Different builds with different parameters (spot time, point distance and beam current) are the basis for this work with the objective generating a process window for dense and crack-free spec-imens. Porosity was characterized based on optical microscope imaging. The occur-rence of a new morphology of porosity which was not observed in traditional melting strategies, was investigated more in detail. Especially the relation between spot time and volume energy was analyzed more in detail. Specimens showing a relative density >99.8% were categorized as dense according to threshold set for this work and were therefore basis for further characterization. Thus, microstructural features were inves-tigated using OM on etched specimens and illustrated by correlating different point distances, volume energies, point energies and spot times. In addition, complementary Hardness tests were performed to gain a basic understanding of the mechanical proper-ties of the produced specimens. As a main result of this thesis, a process window for an EBM point melt strategy is proposed leading to dense specimens showing possibility to tailor the microstructure for desired applications respectively
Keywords: EBM; point melt; Hatch scanning strategy; point distance; spot time; scan strategy; microstructures; porosity; BIP; melt pool; Widmanstätten structure; Basketweave structure